Beyond dogma : Rumi's teachings on friendship with God and early Sufi theories - Mojaddedi, J. A. (Jawid Ahmad) (Oxford University Press, 2012)
Beyond Dogma examines Rumi's central teaching about friendship with God (walaya) in light of earlier Sufi discourse on this topic and its reception by Muslim theologians and jurists. It provides a nuanced and historically contextualized appreciation of Rumi's place in Islam.